Pengaruh Brand Ambassador NCT Dream dan Citra Merek Terhadap Keputusan Pembelian - Andi Juliadi; Masita Aulia; Sintia Ramadhani (MAMEN: Jurnal Manajemen, 2023)
Business competition makes entrepreneurs must be careful in managing strategies in order to compete with their competitors and attract consumers to buy their products. This study aims to determine the effect between Brand Ambassador and Brand Image on Purchasing Decisions. This research uses explanatory research with a quantitative approach. The research sample was taken using a purposive sampling technique with a sample of 103 respondents through questionnaires. In the test the coefficient of determination was obtained (R2) of 0.582, which implies that the influence of the independent variables (brand ambassadors and brand image) on the dependent variable (purchasing decision) is 58.2%, while the remaining 41.8% is influenced by factors other factors outside the variable x. The analysis technique used is multiple linear regression. The results of this study state that: The results of the partial test (t test) show that (1) brand ambassadors influence purchasing decisions, (2) brand image has a significant effect on purchasing decisions, (3) that brand ambassadors and brand image simultaneously (f test ) has a significant effect on purchasing decisions for Lemonilo noodle products.